Opis medyczny jako część ikonosfery - na przykładzie histerii i niepełnosprawności w szpitalu Salpetriere w okresie belle époque = Medical description as part of the iconosphere - the case of hysteria and disability at the Salpetriere Hospital during the Belle Époque - Grabizna, Adrianna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this work I will try to show that one of the driving forces of the social model, would it be in relation to disability or to mental illness, is the disillusionment that scientific description (in this case: coming from medical science) is not objective, but rather depends to a certain degree on concepts prevailing in a worldview, on a culture and values that pertain to a place, a time, and people who construct the description. A scientific description, including medical description, is part of the iconosphere. I will demonstrate this on the hysteria and disability at the Salpetriere Hospital at the time of Belle Époque, especially by the time of Jean-Martin Charcot.
Keywords: histeria; niepełnosprawność; szpital Salpetriere; Charcot, Jean-Martin (1825-1893); hysteria; disability; Salpetriere Hospital